PELATIHAN ZIG-ZAG RUN DRIBBLING DAN PELATIHAN SHUTTLE RUN DRIBBLING SAMA BAIK DALAM MENINGKATKAN KECEPATAN MENGGIRING BOLA FUTSAL SMA DWIJENDRA DENPASAR - Fatchurahman, Reza; Sundari, Luh Putu Ratna; Griadhi, I Putu Adiartha; Tirtayasa, Ketut; Dinata, I Made Krisna; Dwi Primayanti, I Dewa Ayu Inten (Sport and Fitness Journal; Volume 7, No.3, September 2019, 2019)
Futsal is a sport that is popular in the community in performed in many groups, from young children to adults. Futsal is a game that is almost the same as soccer, and now futsal is an international sport, the impact of the entire country playing futsal. This study aims to determine the zig-zag run dribbling training and shuttle run dribbling training equally well in improving Dwijendra Denpasar's high school futsal dribbling skills. This study used an experimental research design Randomized pretest-posttest control group design involving 22 extracurricular swimming students, aged 16-17 years who had good physical fitness. The research subjects were divided into two groups using simple random allocation techniques. Group I was given zig-zag run dribbling training and Group II was given dribbling shuttle run training with the frequency of exercise 3 times a week for 6 weeks. Research shows that the average speed of futsal dribbling in Group I is 23.16 ± 2.7 seconds increasing to 17.36 ± 2.29 seconds and in Group II it is 22.54 ± 2.62 seconds increasing to 18.45 ± 2.20 seconds with a value of p < 0 ,05. This means that there has been a significant and significant increase in training after training. It can be concluded that zig-zag run dribbling training and shuttle run dribbling training are equally good at increasing Dwijendra Denpasar's high school futsal ball speed. Keywords: Zig-zag Run Dribbling, Shuttle Run Dribbling, Speed of herding Futsal Balls